Legal framework for theft of trade secrets and corporate espionage in Malaysia: adhering to the trans pacific partnership agreement (TPPA) - Abd Jalil, Juriah; Mohamed, Duryana; Abdul Rahman, Nasarudin; Raja Mohd Ali, Raja Badrol Hisham; Hassan, Halyani (2019)
Theft of trade secrets and corporate espionage threaten innovation, growth, development and investment of business entities and national economy globally. Civil remedies alone are insufficient to protect trade secrets from this growing threat. As a measure to address this issue, the TPPA requires signatory countries to criminalize theft of trade secrets and corporate espionage. In Malaysia civil remedies under the common law of breach of confidence and employment contract, protects the owner’s right against any misappropriation of trade secrets. However there is no law to criminalize theft of trade secrets and corporate espionage in Malaysia. This research is undertaken to establish a legal framework to criminalize theft of trade secrets and corporate espionage apart from analyzing the protection of trade secrets in Malaysia